STORY OF BIG FLOOD IN THE MODERN INDONESIAN LITERARY: AN ECOCRITICISM STUDY - Rohman, Saifur (IJLECR (International Journal of Language Education and Cultural Review), 2015)
The nature of paper shows that Ecocriticism is not popular issue in the modern Indonesian criticism. Hence, it is very crucial to develop the Indonesian criticism based on the ecological perspective because nowday that the term development is synonym with exploiting the nature. The paper is to find out the ecological issue in the modern indonesian literary, especially in fiction prose and poems publised for late ten years. To analyze the work, researcher is used semiotic method and hermeneutic design of research as an approach. Semiotic will investigate the symbol behind the words and hermeneutic will translated the symbol to actual message. Based on the analysis, the ecological theme in the modern Indonesian literary is crucial interpretation. The meaning appeared in the work has given the imporant values of increasing care of nature, human kind, and harmonization. For recomentation, in the future researcher should have interpretate the work based on the ecocriticism to increase meaning of human and nature.